Implications of Schwann Cells Biomechanics and Mechanosensitivity for Peripheral Nervous System Physiology and Pathophysiology - Rosso, Gonzalo; Young, Peter; Shahin, Victor (Frontiers in Molecular Neuroscience, 2017)
The presence of bones around the central nervous system (CNS) provides it with highly effective physiologically crucial mechanical protection. The peripheral nervous system (PNS), in contrast, lacks this barrier. Consequently, the long held belief is that the PNS is mechanically vulnerable. On the other hand, the PNS is exposed to a variety of physiological mechanical stresses during regular daily activities. This fact prompts us to question the dogma of PNS mechanical vulnerability. As a matter of fact, impaired mechanics of PNS nerves is associated with neuropathies with the liability to mechanical stresses paralleled by significant impairment of PNS physiological functions. Our recent biomechanical integrity investigations on nerve fibers from wild-type and neuropathic mice lend strong support in favor of natural mechanical protection of the PNS and demonstrate a key role of Schwann cells therein. Moreover, recent works point out that SCs can sense mechanical properties of their microenvironment and the evidence is growing that SCs mechanosensitivity is important for PNS development and myelination. Hence, Schwann cells exhibit mechanical strength necessary for PNS mechanoprotection as well as mechanosensitivity necessary for PNS development and myelination. This mini review reflects on the intriguing dual ability of Schwann cells and implications for PNS physiology and pathophysiology.